2D Nanosilicates Loaded with Proangiogenic Factors Stimulate Endothelial Sprouting. Issue 7 (11th June 2018) - Howell, David W.; Peak, Charles W.; Bayless, Kayla J.; Gaharwar, Akhilesh K.
Abstract: Therapeutic angiogenesis remains a major clinical challenge due to lack of biomaterials to sequester and deliver proangiogenic therapeutics. Here, 2D nanosilicates are introduced as a platform technology to sequester and deliver a multitude of proangiogenic growth factors to stimulate angiogenesis. The high surface area and charged characteristics of nanosilicates prolong release of proangiogenic molecules. Interestingly, nanosilicates can maintain bioavailability compared to exogenously delivered biomolecules. Incorporation of therapeutics‐loaded nanosilicates within collagen hydrogels stimulates endothelial cell invasion in a 3D in vitro models of angiogenesis. The results show that endothelial cell invasion is controlled predominately by the type of growth factors conjugated to the nanosilicates. Overall, this work illustrates the importance of nanosilicates as a platform technology to noncovalently conjugate proangiogenic therapeutics to direct angiogenesis. Abstract : 2D nanosilicates as a platform technology to sequester and deliver a multitude of proangiogenic growth factors to stimulate angiogenesis are presented. The high surface area and charged characteristics of 2D nanosilicates prolong the release of proangiogenic molecules, while maintaining its bioavailability.